2019
DOI: 10.3346/jkms.2019.34.e70
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Value of Admission Blood Glucose Level in Critically Ill Patients Admitted to Cardiac Intensive Care Unit according to the Presence or Absence of Diabetes Mellitus

Abstract: Background Admission blood glucose (BG) level is a predictor of mortality in critically ill patients with various conditions. However, limited data are available regarding this relationship in critically ill patients with cardiovascular diseases according to diabetic status. Methods A total of 1,780 patients (595 with diabetes) who were admitted to cardiac intensive care unit (CICU) were enrolled from a single center registry. Admission BG level was defined as maximal s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…Admission ICU BGL was a predictor for mortality in critically ill patients. In ST-segment elevation myocardial infarction complicated by cardiogenic shock, admission BGL is an independent predictor of increased risk of death only among patients without DM [27], Kim and colleges also found admission BGL was associated with increased cardiac ICU mortality in non-DM critically ill individuals but not in critically ill patients who had DM [28]. In our research, we demonstrated patients with a history of DM in comparison with nondiabetics had signi cantly higher crude ICU mortality rate when the rst ICU admission glucose levels were low (i.e., < 103 mg/dL).…”
Section: Discussionmentioning
confidence: 94%
“…Admission ICU BGL was a predictor for mortality in critically ill patients. In ST-segment elevation myocardial infarction complicated by cardiogenic shock, admission BGL is an independent predictor of increased risk of death only among patients without DM [27], Kim and colleges also found admission BGL was associated with increased cardiac ICU mortality in non-DM critically ill individuals but not in critically ill patients who had DM [28]. In our research, we demonstrated patients with a history of DM in comparison with nondiabetics had signi cantly higher crude ICU mortality rate when the rst ICU admission glucose levels were low (i.e., < 103 mg/dL).…”
Section: Discussionmentioning
confidence: 94%
“…RBG interferes with blood flow in the culprit vessel and is linearly correlated with the TIMI blood flow index [23]. Some studies have indicated that RBG on admission is closely related to mortality in nondiabetic patients [24].…”
Section: Discussionmentioning
confidence: 99%
“…Our results are in line with studies investigating the prognostic value of ABG on intracerebral hemorrhage, myocardial infarction, and other critical conditions. [ 1 ] The likely explanations for this are as follows: first, higher ABG in non-diabetes, usually defined as stress hyperglycemia, tends to occur in patients with critical illness. Second, diabetic patients with long-term exposure to increased glucose may have reduced the adverse effects of hyperglycemia on metabolism.…”
mentioning
confidence: 99%